AOCS Requirements and Practical Limitations for High-Speed Communications on Small Satellites - Fernando Aguado-Agelet; Andrés Eduardo Villa; Marcos Arias-Acuña; Francisco Javier Díaz-Otero (International Journal of Aerospace Engineering)
In recent years, an increasing number of countries have shown a growing interest in developing their indigenous space capacity building through national small satellite programs. These satellites, which were initially focused on educational and training missions, currently are more scientific and operational-oriented. Thus, small satellite missions are being considered not only as educational tools but also as technological demonstrators or, even, mature enough for commercial and scientific missions, which might generate a huge amount of data to be transmitted to the ground segment. Therefore, an increasing demand on channel capacity will be needed for downloading the generated housekeeping and scientific data for missions based on small satellites. This paper analyses the communication subsystem of a real Cubesat. The influence of geometrical parameters is rigorously calculated both in the signal-to-noise ratio and in the capacity to transmit information. Subsequently, which parameters of the radio link can be modified to increase the transmission capacity, including the pointing requirements and its practical implementation, is studied. Finally, and as a future line, the technical feasibility of using optical links on small satellites that might greatly increase the transmission capacity, including the satellite pointing problems that presents, is presented. In conclusion, this paper presents a rigorous calculation in different frequency bands of the signal-to-noise ratio and the pointing accuracy that is needed to achieve the maximum transmission speed from the satellite to the ground station, and therefore the requirements that the Attitude and Orbital Control Systems (AOCS) must have, as well as the limitations of current systems.